2021
DOI: 10.1016/j.apsb.2020.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Design, synthesis, and biological evaluation of quinazolin-4(3H)-one derivatives co-targeting poly(ADP-ribose) polymerase-1 and bromodomain containing protein 4 for breast cancer therapy

Abstract: This study was aimed to design the first dual-target small-molecule inhibitor co-targeting poly (ADP-ribose) polymerase-1 (PARP1) and bromodomain containing protein 4 (BRD4), which had important cross relation in the global network of breast cancer, reflecting the synthetic lethal effect. A series of new BRD4 and PARP1 dual-target inhibitors were discovered and synthesized by fragment-based combinatorial screening and activity assays that together led to the chemical optimization. Among these compounds, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
49
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(51 citation statements)
references
References 71 publications
2
49
0
Order By: Relevance
“…Here, the cyano group could be extended to interact with Asn165. Since computer-aided drug design plays an important role in drug discovery, 27 we also conducted molecular docking experiments on this tubulin complex. A series of ELR510444 derivatives with different substituents was designed and docked into the CBS by Autodock Vina.…”
Section: Resultsmentioning
confidence: 99%
“…Here, the cyano group could be extended to interact with Asn165. Since computer-aided drug design plays an important role in drug discovery, 27 we also conducted molecular docking experiments on this tubulin complex. A series of ELR510444 derivatives with different substituents was designed and docked into the CBS by Autodock Vina.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, inhibitors of PARP1 together with the DNA damage response kinases ATR, CHK1 or WEE1 are being investigated in clinical trials [ 225 ]. Dual inhibitory molecules, co-targeting PARP1 and Bromodomain 4 (BRD4), which executes key functions in multiple processes including DNA damage responses, or PARP1 and RAD51, the key recombinase in HR, have been found to sensitize MBC cell lines regardless of hormone receptor status, BRCAness, or acquired resistance [ 226 , 227 ]. Suggesting the validity of these concepts for the eradication of CTCs, Gong and colleagues [ 149 ] demonstrated that chemoresistance due to the enhanced DNA repair in CTCs versus primary BC can be broken by adding inhibitors of the DNA damage response kinases CHK1 or CHK2.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…Therefore, the expression of key oncogenes can be inhibited through the displacement of BRD4 from chromatin. Accumulative evidence indicates that BRD4 protein has been implicated in various human diseases, including acute myeloid leukemia (AML) [ 8 10 ], prostate cancer [ 11 , 12 ], breast cancer [ 13 15 ], gastrointestinal stromal tumor (GIST) [ 16 ], neuroblastoma [ 17 ], pancreatic cancer [ 18 , 19 ], cholangiocarcinoma [ 20 ] as well as inflammations [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%